Biogas from microalgae: Technologies, challenges and opportunities. (January 2020) - Zabed, Hossain M.; Akter, Suely; Yun, Junhua; Zhang, Guoyan; Zhang, Yufei; Qi, Xianghui
Abstract: Production of biogas from microalgae has been receiving significant attention since 1950s, as microalgae are capable of rapidly growing in the non-arable land area and accumulating high quantity of digestible macromolecules in the biomass. Nevertheless, commercial production of microalgae-based biogas is still in its immature stage for some existing technoeconomic challenges, as exemplified by the requirement of a costly and energy consuming step in biomass harvesting, recalcitrance of the components, low biomass loading rate, and interferences of various operational factors. Real-world research and developments are therefore necessary for achieving a state-of-the-art technology to produce microalgal biogas. In this context, extensive research efforts have been devoted since decades as attempts to improve efficiency and sustainability of this bioprocess. This paper presents a critical and comprehensive review on the key issues and perspectives of microalgal biogas in terms of current knowledge and future developments. Over the contemporary reviews published on this topical area, present paper distinctly covers almost all the relevant aspects, which might draw a complete picture on microalgal biogas and provide necessary perspectives for conducting further research efforts. Specifically, this paper discusses potentials of microalgae as the biogas feedstocks, screening and selection approaches of potent strains, technological aspects of microalgal biogas production, reactor design for anaerobic digestion (AD), operational conditions affecting AD, strategies for improving strains and biogas yield, biogas upgrading, kinetics, modelling and economics, life cycle assessment (LCA), and challenges coupled with further research opportunities. Highlights: Microalgae have been using as potential biogas feedstocks for more than 60 years. High harvesting cost and low biomass yield are major technical hurdles for algae. Reactor design and optimum operational conditions can affect biogas yield. Pretreatment, co-digestion and strain-improvement can increase biogas yield. Kinetics, economics and life cycle assessment are important for large-scale production.